Friday

April 18, 2014

April 18, 2014

Posted by **Tara** on Sunday, January 10, 2010 at 12:31pm.

2cos^2x+3cosx=0

sq. root of (cos^2x)+(cosx)=sq. root of (-3/2)

2cos=(sq. root of -3 times sq. root of 2)/2)) times 2/1

cos=(2 times sq. root of -3 times sq. root of two)/2))

**Related Questions**

Algebra - I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1...

Algebra - Can you explain how to find the solution of 3x^2-2x+5, using the ...

Trig. - 2sin^2x-3sinx=-1 sin^2x-3sinx=-1/2 times -3 sq. root of (sin^2x)+sinx= ...

Calculus I - Find the derivative ** (sq root) y = (square root) x + (2nd sq root...

Algebra - I had to solve the function g of f where f is x^2+1 and g is sq. root ...

Trigonometry - I'm trying to find the cosecant of 11 pi/6. The answer is -2, but...

Math - 1) Solve equation 3r+5 _____ + 2 = 2r to find the value of r? 2 A. 2 1/7 ...

Roots and Pre-cal - Find the roots of the function f(x)= x^2 +2x+2 a)-1 + sq ...

math - simplify square 48/square6 square root(48) is the same as sq root (8) x ...

Math - Which of these is an irrational number? A.. Sq root of 14 B. -sq root of ...